Characterization of an Amorphous Titanium Oxide Film Deposited onto a Nano-Textured Fluorination Surface - Li, Pei-Yu (Materials (Basel), 2016)
The photocatalytic activity of an amorphous titanium oxide (a-TiO(x)) film was modified using a two-step deposition. The fluorinated base layer with a nano-textured surface prepared by a selective fluorination etching process acted as growth seeds in the subsequent a-TiO(x) deposition. A nanorod-like microstructure was achievable from the resulting a-TiO(x) film due to the self-assembled deposition. Compared to the a-TiO(x) film directly deposited onto the untreated base layer, the rate constant of this fluorinate-free a-TiO(x) film surface for decomposing methylene blue (MB) solution that was employed to assess the film’s photocatalytic activity was markedly increased from 0.0076 min(−1) to 0.0267 min(−1) as a mechanism for the marked increase in the specific surface area.